ANALISIS KEMAMPUAN MEMECAHKAN MASALAH MELALUI PEMBELAJARAN SOCIAL LEARNING UNTUK MENINGKATKAN INOVASI BERWIRAUSAHA DAN KREATIVITAS PADA MAHASISWA EKONOMI DI KOTA MAKASSAR - Andi Tenri Ampa; Muhammad Hasan; Nurjannah; Nur Arisah; Andi Annisa Sulolipu (Universitas Negeri Makassar, 2023)
This study aims to find out whether various universities apply social learning methods in lectures and to find out how students respond to learning based on social learning methods. In this study, researchers obtained data from students of the Faculty of Economics and Business at several universities in Makassar by using observation and descriptive techniques which are included in the type of qualitative research. The scope of the research area includes the location where the research is located, namely the Faculty of Economics and Business (FEB) in the city of Makassar. The research results obtained are the effect of problem-solving skills through social learning on increasing entrepreneurial innovation and creativity in economics students in the city of Makassar, participants in the entrepreneurship program are more likely than non-participants to have a higher attitude or intention to start their own business four or five years after their studies are completed which, even if accompanied by social learning itself, will show a clear difference between these differences.